Perencanaan Produksi dengan Run Out Time (ROT) untuk Menekan Biaya Persediaan Bahan Baku pada UMKM Camel Mandiri - Kurniawan, David Elvando Daniel; Mundari, Siti (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Camel Mandiri is an industrial home engaged in manufacturing that produces products in the form of Adjuster bolts and Adjuster nails. The raw materials used by the business he runs are in the form of bolts, nails, and HDPE plastic pellets which are processed using a semi-injection machine. Camel Mandiri is currently experiencing problems in planning a production plan for the products it produces. Fluctuating demand and the absence of proper production planning make companies experience excess and shortage of product inventory, if they experience excess production, it will cause the accumulation of inventory in the storage space. With the accumulation of inventory, the production process is stopped due to insufficient storage space. This study aims to provide a proposal for the right production planning in the order of the production process with the Run Out Time (ROT) method to calculate and determine which products will be produced first in order to meet all consumer demands according to the production capacity and it is expected that all finished product supplies will run out at the same time. Some of the improvement scenarios in production planning carried out are the second scenario, namely weekly production, while the second scenario uses production on a 10-day working basis. The amount of costs obtained / incurred from the second scenario in reducing the cost of raw materials is Rp. 678,395,913,-. These results are smaller than those obtained by companies that do not have aggregates in their production planning.